¿Explica el trabajo la sociedad? - Jorge García López (Universidade do Porto, 2009)
This article introduces some of the work and sociological research of Pierre Naville (1904-1993) on employment and automation skills. On the basis of Naville´s research, this paper aims to discuss critically the construction of the object characteristic of the classical Soci-ology of Work. It argues that sociologically relevant ´work´ is one which refers to a general social mediation, similar to the concept of ´abstract work´ in the late writings of Marx.